Balance and perspectives of bilingual education in Puno - López, Luis Enrique (1987)
This paper attempts a brief characterization of a bilingual educational experience that has been taking place for almost six years in the southern region of the Peruvian Sierra, in the department of Puno. Throughout the exhibition we will make a brief account of the way in which this experience began, its development and the current situation. We will also describe the methods and materials used in the application of bilingual education in Puno, from a presentation of the postulates that support it. Finally, we will attempt a kind of balance of the experience and we will present our point of view regarding the perspectives that this type of work has in the current socio-political reality of the country.